simplify (cosx/1+sinx)+(1+sinx/cosx)

DofotheroU 2020-12-28 Answered

simplify (cosx/1+sinx)+(1+sinx/cosx)

You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Expert Answer

Faiza Fuller
Answered 2020-12-29 Author has 108 answers

(cosx/1+sinx)+(1+sinx/cosx)=(cosx/1+sinx)+((cosx+sinx)/cosx)
=(cos2x+(1+sinx)(cosx+sinx))/cosx(1+sinx)
=(cos2x+cosx+sinx+sinxcosx+sin2x)/cosx(1+sinx)
=(1+cosx+sinx+sinxcosx)/cosx(1+sinx)
=(1+cosx+sinx(1+cosx))/cosx(1+sinx)
=(1+cosx)(1+sinx)/cosx(1+sinx)
=(1+cosx)/cosx
=1+secx

Not exactly what you’re looking for?
Ask My Question

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

New questions